The mir-767-105 cluster: a crucial factor related to the poor prognosis of hepatocellular carcinoma - Tao Rui; Siyi Xu; Shi Feng; Xueyou Zhang; Haitao Huang; Qi Ling (BMC, 2020)
Abstract MiRNAs have been widely reported as the therapeutic target for hepatocellular carcinoma (HCC). However, mirna clusters, as the more impressive tumor regulatory factors, have received little attention. By deeply digging the Cancer Genome Atlas (TCGA) database, we aimed to explore the vital mirna cluster that regulated the poor prognosis of HCC. The results showed that the upregulation of mirna cluster-767-105 in HCC was the most significant, compared with the non-tumor tissues. Besides, high expression of all three members of the cluster was positively correlated with poor prognosis of HCC and the resistance of sorafenib. Cox analysis proved that all the three mirnas were independent prognostic factors, while the mir-767 was the most compelling (HR value 8.388, 95%CI 2.524-27.897). The higher expression of the three-mirna signature also significantly indicated the worse prognosis. Through bioinformatics analysis, we screened their common potential target genes, which were highly correlated with tumor regulation. These results supported that the mirna cluster-767-105 promoted the poor outcome of HCC and could be a robust target for the therapy of HCC patients.